2020
DOI: 10.1186/s43058-020-00044-2
|View full text |Cite
|
Sign up to set email alerts
|

Implementation opportunities and challenges identified by key stakeholders in scaling up HIV Treatment as Prevention in British Columbia, Canada: a qualitative study

Abstract: Background: The province of British Columbia (BC), Canada, was among the first jurisdictions to scale up HIV Treatment as Prevention (TasP) to the population level, including funding and policy commitments that enhanced HIV testing efforts (e.g., expansion of routine, opt-out testing), while also making antiretroviral therapy universally available to all people living with HIV. As such, BC represents a critical context within which to identify factors that influenced the scalability of TasP (e.g., acceptabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 27 publications
1
6
0
Order By: Relevance
“…It is also consistent with the original SAIA trial which found that "investments in infrastructure and human resources [could] be critical to improve prevention of mother-to-child HIV transmission service delivery and protect infants from HIV" (34), particularly in low performing health facilities in other African countries, including where SAIA-SCALE was implemented in Mozambique (8). These ndings are also consistent with those documented in other studies on the scale-up of pediatric and adult HIV interventions across the world, that highlight the shortcomings of believing in the technological x and call for the need to attend to the importance of contextual factors that mediate intervention uptake and scale-up (11)(12)(13).…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…It is also consistent with the original SAIA trial which found that "investments in infrastructure and human resources [could] be critical to improve prevention of mother-to-child HIV transmission service delivery and protect infants from HIV" (34), particularly in low performing health facilities in other African countries, including where SAIA-SCALE was implemented in Mozambique (8). These ndings are also consistent with those documented in other studies on the scale-up of pediatric and adult HIV interventions across the world, that highlight the shortcomings of believing in the technological x and call for the need to attend to the importance of contextual factors that mediate intervention uptake and scale-up (11)(12)(13).…”
Section: Discussionsupporting
confidence: 88%
“…Like for intervention implementation, the scale-up of HIV-related interventions across high income and low-and middle-income countries calls for the need to attend to the importance of contextual factors that mediate intervention uptake and scale-up (11)(12)(13). A comparative analysis of the scale-up on an mHealth intervention that uses SMS communication to improve patient adherence to medication and engagement in care in Canada and Kenya, showed, even with robust research evidence, scale-up was a precarious and uncertain process, embedded within the wider politics and nancing of Canadian and Kenyan health systems (11).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Participants were employed at community hospitals (major teaching, minor teaching, and nonteaching) [ 16 ], federal government hospitals, private practices, and regional medical centers located across NC. We used a stratified purposeful sample to recruit prescribers in order to explore variations on experiences from those with different training and patient populations [ 17 , 18 ]. We employed multiple strategies for sampling prescribers; this included sampling the four most common subspecialties providing outpatient opioid prescriptions for acute and post-surgical pain in NC (i.e.…”
Section: Methodsmentioning
confidence: 99%